Perceived Causes of Cancer and Corresponding Behavioral Changes: A Qualitative Study on Breast Cancer Survivors in Taiwan. (1st October 2022) - Niu, Jasmine; Chen, Duan-Rung; Lo, Chiao; Cheng, Shao-Yi; Huang, Chiun-Sheng
Objectives: Breast cancer is the most common cancer among women in Taiwan, and treatment and coping with the disease become prominent features in a survivor's life. Here, we examined Taiwanese survivors' perceived causes of breast cancer, the influence of support networks on their perceptions, and the behavioral changes they made to prevent recurrences. Methods: In this qualitative study, we used an explanatory approach involving semi-structured in-depth interviews based on grounded theory. We recruited (via physician referrals) 29 survivors aged ≥20 who had received their initial diagnosis at least 6 months earlier. Results: Although the participants had made behavioral changes in many areas of their lives after diagnosis, most still believed that "stress and emotions" were the most crucial factor in causing cancer. They strongly emphasized reducing stress levels to prevent recurrences. However, when maintaining healthy behaviors became stressful, they chose to level off healthy lifestyles for the sake of their emotional well-being. They made career changes to improve their quality of life yet continued to experience a deep fear of recurrence. Adopting behavioral changes leading to healthy lifestyles and following regular follow-ups helped to reduce their anxiety concerning recurrence. Conclusion: The participants' behavioral changes were strongly associated with the perceived causes of cancer. Health-promotion programs aimed at breast cancer prevention should focus on participants' subjective perception of the cause of cancer.